KEBIJAKAN HUKUM PIDANA SEBAGAI UPAYA MEMINIMALISIR TINDAK PIDANA BULLYING DI MEDIA ELEKTRONIK - Sumangat Salomo Sidauruk; July Esther; Herlina Manullang (Magister Hukum Universitas HKBP Nommensen, 2021)
The need for technology today is increasing and continues to be developed in order to make it easier for humans to carry out their daily activities, because apart from being a medium for providing information, through the Internet, commercial community activities will also become the largest and fastest growing part and can penetrate various national borders. In fact, the existence of some types of business is impossible without this network, market activities in the world can be known for 24 (twenty four) hours. But in reality what is happening today, the development of this era is like a double-edged sword because for the positive we all have to be grateful for it because there are many benefits and conveniences obtained from this technology, for example we can do banking transactions anytime with e-banking, e-commerce It also makes it easy for us to buy or sell an item without knowing the place. In addition, we can find references or information about science is not difficult with the e-library and many more conveniences obtained with the development of the internet. Whereas in a negative nature, the use of this information technology has influenced every attitude and behavior of members of the community, even as a result has also formed a new world society that is no longer hindered by the territorial boundaries of a country to become a